Should we mine the deep seafloor?. Issue 7 (13th July 2017) - Beaulieu, Stace E.; Graedel, T. E.; Hannington, Mark D.
Abstract: As land‐based mineral resources become increasingly difficult and expensive to acquire, the potential for mining resources from the deep seafloor has become widely discussed and debated. Exploration leases are being granted, and technologies are under development. However, the quantity and quality of the resources are uncertain, and many worry about risks to vulnerable deep‐sea ecosystems. Deep‐sea mining has become part of the discussion of the United Nations Sustainable Development Goals. In this article we provide a summary of benefits, costs, and uncertainties that surround this potentially attractive but contentious topic. Key Points: Momentum is growing toward the emergence of a deep‐sea mining industry There is continuing debate about sustainable exploitation of seabed resources, and whether their development is worth the ecological risk Many aspects of resource extraction and environmental regulation remain too uncertain to optimally aid decision‐making